S1 guidelines "lumbar puncture and cerebrospinal fluid analysis" (abridged and translated version). - Tumani, Hayrettin; Petereit, H. F.; Gerritzen, A.; Gross, C. C.; Huss, Andre M.; Isenmann, S.; Jesse, S.; Khalil, Michael; Lewczuk, Piotr; Lewerenz, Jan; Leypoldt, Frank; Melzer, Nico; et al. (Neurological Research and Practice, 2020)
Introduction: Cerebrospinal fluid (CSF) analysis is important for detecting inflammation of the nervous system and the meninges, bleeding in the area of the subarachnoid space that may not be visualized by imaging, and the spread of malignant diseases to the CSF space. In the diagnosis and differential diagnosis of neurodegenerative diseases, the importance of CSF analysis is increasing. Measuring the opening pressure of CSF in idiopathic intracranial hypertension and at spinal tap in normal pressure hydrocephalus constitute diagnostic examination procedures with therapeutic benefits.Recommendations (most important 3-5 recommendations on a glimpse): The indications and contraindications must be checked before lumbar puncture (LP) is performed, and sampling CSF requires the consent of the patient.Puncture with an atraumatic needle is associated with a lower incidence of postpuncture discomfort. The frequency of postpuncture syndrome correlates inversely with age and body mass index, and it is more common in women and patients with a history of headache. The sharp needle is preferably used in older or obese patients, also in punctures expected to be difficult.In order to avoid repeating LP, a sufficient quantity of CSF (at least 10 ml) should be collected. The CSF sample and the serum sample taken at the same time should be sent to a specialized laboratory immediately so that the emergency and basic CSF analysis program can be carried out within 2 h.The indication for LP in anticoagulant therapy should always be decided on an individual basis. The risk of interrupting anticoagulant therapy must be weighed against the increased bleeding risk of LP with anticoagulant therapy.As a quality assurance measure in CSF analysis, it is recommended that all cytological, clinical-chemical, and microbiological findings are combined in an integrated summary report and evaluated by an expert in CSF analysis. Conclusions: In view of the importance and developments in CSF analysis, the S1 guideline "Lumbar puncture and cerebrospinal fluid analysis" was recently prepared by the German Society for CSF analysis and clinical neurochemistry (DGLN) and published in German in accordance with the guidelines of the AWMF (https://www.awmf.org). /uploads/tx_szleitlinien/030-141l_S1_Lumbalpunktion_und_Liquordiagnostik_2019-08.pdf). The present article is an abridged translation of the above cited guideline. The guideline has been jointly edited by the DGLN and DGN.
EVALuna2:384003